Dealing with dental implant failures - Liran Levin (University of São Paulo, 2008)
An implant-supported restoration offers a predictable treatment for tooth replacement. Reported success rates for dental implants are high. Nevertheless, failures that mandate immediate implant removal do occur. The consequences of implant removal jeopardize the clinician's efforts to accomplish satisfactory function and esthetics. For the patient, this usually involves further cost and additional procedures. The aim of this paper is to describe different methods and treatment modalities to deal with dental implant failure. The main topics for discussion include identifying the failing implant, implants replacing failed implants at the exact site, and the use of other restorative options.When an implant fails, a tailor made treatment plan should be provided to each patient according to all relevant variables. Patients should be informed regarding all possible treatment modalities following implant failure and give their consent to the most appropriate treatment option for them.